Grazing Behavior and Itineraries of Kacang Goat with Different Coat Color under Semi Intensive Management - Kiswanto, Slamet Heri; Baihaqi, Muhammad; Prihantoro, Iwan (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
The objective of this research was to analyze the effect of coat color on behavior and itineraries of kacang goat during grazing time. This research used 9 females and 3 males kacang goat. Behavior observed by one zero sampling method and analyzed using t-Test at level 5%. The result indicated that ingestion and browsing of brown goat (30.91±2.87%; 8.75±3.10%) higher than black goat (28.57±2.69%; 6.07±4.78%), while black goat showed more locomotion (33.26±4.50%) than brown goat (29.70±4.63%). Grazing, panting, and resting behaviors, and distance traveled of black goat (22.56±2.63%; 4.48±4.02%; 2.34±2.97%; 483.48±133.16 m) were not different with brown goat (22.16±2.90%; 4.59±3.71%; 2.64±1.52%; 392.29±81.19 m). Result also indicated that goat showed more grazing than browsing with high preference in you ng grass than old grass, legume, and weed.